A systematic review and meta-analysis of antibiotic resistance patterns, and the correlation between biofilm formation with virulence factors in uropathogenic E. coli isolated from urinary tract infections. (July 2020) - Zhao, Fei; Yang, Huanxin; Bi, Dezhong; Khaledi, Azad; Qiao, Mingqi
Abstract: Urinary tract infection (UTI) is caused by the invasion of the pathogen in the urinary system that can manifest as symptomatic or asymptomatic bacteriuria. This study was conducted to investigate antibiotic resistance patterns, and the correlation between biofilm formations with virulence factors in uropathogenic E. coli isolates retrieved from UTI. We searched Scopus and Google Scholar, PubMed, Web of sciences for studies published in the English language between 1st 2005 to 31st December 2019. The Mesh terms and text words included "biofilms", OR "biofilm formation", AND "antibiotic resistance", OR "drug-resistance", OR "antimicrobial drug resistance", AND "urinary tract infections", OR "UTI", AND "biofilm related-genes", AND "virulence factors" AND "correlation", AND "Uropathogenic Escherichia coli", OR "Uropathogenic E. coli " AND "prevalence" AND "Iran". Data analyzed using Comprehensive Meta-Analysis (CMA) software. The random-effects model was used to calculate the pooled prevalence with 95% confidence interval (CI). The combined rates of biofilm formation in Uropathogenic E. coli (UPEC) isolates were achieved as 84.6% (95% CI: 72.7–91.9). Also, 24.8%, 26.1% and 44.6% of UPEC isolates were able to create strong, moderate and weak biofilm, respectively. The highest pooled antibiotic resistance was against Ampicillin followed by Tetracycline with resistance rates of 74.6% and 64.9%, respectively. Accordingly, some studies reported that biofilm production was significantly associated with antibiotic resistance and virulence genes (p < 0.05). This study showed a high tendency among UPEC isolates to form biofilm (more than 84%), also, most studies included in the present review reported a significant correlation between biofilm formation with antibiotic resistance and virulence factors. Highlights: The combined rate of biofilm formation in UPEC isolates was 84.6%. About 24.8%, 26.1% and 44.6% of UPEC isolates were able to create strong, moderate and weak biofilm, respectively. Studies reported the correlation between biofilm formation and antibiotic resistance.